Defense Of Digital Business Morals and Ethics Based On Chess Paramitha - Arta, I Putu Sugih (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
The demographic bonus that will occur in the future is certain to be filled by the Gen-Z population who are very familiar with the digital world as a guide in their activities. Life really depends on the role of digital business. The business world will note new entrants who survive and disappear in a relatively quick time. Likewise, the business profession will enter areas without the scientific discipline they are engaged in, thus potentially causing conflict. To achieve ideal business goals, one must pay attention to the correct ideological superstructure (Sandeson, 2003:60) in accordance with moral teachings in religious life. Hinduism and Buddhism recognize the term Catur Paramitha, namely metta (Buddhist) or maîtri (Hindu), Karuna, Upeksa and Muditha. If the teachings of Catur Paramitha are digitized from an early age, they will help lay the foundation for religious values applied to business activities. The process of maintaining morals cannot be done instantly,because it takes a long time to go through the phases of an individual human life. The digital world, which is an alternative teacher for the Gen-Z age population, must of course have started the change by introducing the teachings of Catur Pramitha from an early age in the form of animated film visualizations up to adulthood with adult films containing the teachings of Catur Paramitha. It is hoped that the implications of this teaching will provide a strong ethical foundation inbusiness, a business person understands the elements of business by applying the values of friendship (maîtri/metta), love (karuna), sympathy (muditha) and tolerance (upeksha).